2008
DOI: 10.1243/09544062jmes772
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear thermo-mechanical cylindrical bending of functionally graded plates

Abstract: Based on the first-order non-linear von Karman theory, cylindrical bending of functionally graded (FG) plates subjected to mechanical, thermal, and combined thermo-mechanical loadings are investigated. Analytical solutions are obtained for an FG plate with various clamped and simply-supported boundary conditions. The closed form solutions obtained are very simple to be used in design purposes. The material properties are assumed to vary continuously through the thickness of the plate according to a power-law d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…shows the results for center deflection of an FG plate under thermal loading ()Pz=0 by using the two‐parameter expansion in . It is observed that the results are of good accuracy in comparison with the exact solution . In addition, when deflection and normal stress resultant are used as the perturbation parameters, the method is accurate even with the second‐order expansion.…”
Section: Numerical Results and Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…shows the results for center deflection of an FG plate under thermal loading ()Pz=0 by using the two‐parameter expansion in . It is observed that the results are of good accuracy in comparison with the exact solution . In addition, when deflection and normal stress resultant are used as the perturbation parameters, the method is accurate even with the second‐order expansion.…”
Section: Numerical Results and Discussionmentioning
confidence: 84%
“…The results of seven different analyses of a simply‐supported FG plate under thermal loading, including the one‐parameter expansion of N T and T c with different perturbation parameters (deflection w(x1), rotation ψ(x2), and normal stress resultant N x ) and the two‐parameter expansion of N T and M T , for center deflection and axial stress versus ΔT are displayed and compared with the exact solution in Figs. and , respectively.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations